Matemática e música e o ensino de funções trigonométricas - Depizoli, Carlos Antonio (2015)
Using the relationship between Mathematics and Physics and having music as a source of features associated with mathematical concepts, this work aims to contribute to the development of skills in students who are learning mathematical subjects such as trigonometric functions. Important concepts related to acoustics are presented, showing the importance of Continuous Fourier Series (CFS) in the development of Additive Synthesizer and its use in trigonometry.